Ayurvedic Management of Hypothyroidism - A Case Report - Meghna; Lalit Nagar; Ringzin Lamo; Kamal Nayan Dwivedi (Krupanidhi College of Pharmacy, 2023)
Hypothyroidism is the significant endocrine problem found in general public. It is characterized by insufficient production of thyroid hormones, leading to abnormal levels. This condition prompts the decrease in Basal metabolic rate of the body. Ayurveda places a significant part to preclude the basic reason and to treat it. In Ayurveda, it tends to be associated with Kapha-vata dosha dushti, Rasavaha Strotasadushti, Medadushti and Agnimandya. In present study, a 22 years old female patient suffering from Sthaulya (~Weight gain), Duarbalya (~Weakness), Twak rukshata (~Dry skin), Kesh patana (hair loss), puffiness around eyes, mood swings, impaired memory, emotional depression, drowsiness, headache, Amalapitta (~Hyperacidity) and lethargy from last three years. She had been taking allopathic medicine without experiencing any satisfactory relief in her symptoms. In the present study, group of Herbo-mineral preparation was prescribed to the patient for a period of 4 months. After four months patient experienced relief, and her allopathic medicine was completely stopped. Keywords: Hypothyroidism, Agnimandya, Sthaulya